Máquinas, morte e altivez: o letramento literário através do fantástico mundo de José J. Veiga e Murilo Rubião - Rosa, Sandra Rocha Martins (Universidade Federal de Catalão, 2021)
In Máquinas, Morte e Altivez: literary literacy through the fantastic world of José J. Veiga and Murilo Rubião, we make suggestions for the formation of a critical reader based on theoretical supports. We defend that reading is an act of fundamental importance for the entire literate society, as it is through reading that the formation of the critical individual is obtained. As this habit is increasingly restricted, this research defends the use of literary literacy from fantastic literature for the formation of subject readers from the short story genre, since its structural form and short and fast reading can be a contributor in arousing the reader's interest. We have as narrative corpus of authors José J. Veiga and Murilo Rubião representatives of this literary writing that works with unusual and unheard of elements. The analysis of the short stories by Veiga and Rubião, authors who deal with human relationships and their peculiarities from social criticism, shows that literature is the place of escape from human torments. It is in it that the individual is transformed, therefore, we reinforce that the practice of literary literacy is relevant for the formation of the individual, as well as his collaboration in social transformations.
Keywords: Letramento Literário; Conto; Literatura Fantástica; 8.01.00.00-7